Revaluing donor and recipient bodies in the globalised blood economy: Transitions in public policy on blood safety in the United Kingdom. (January 2014) - Busby, Helen; Kent, Julie; Farrell, Anne-Maree
The clinical use of blood has a long history, but its apparent stability belies the complexity of contemporary practices in this field. In this article, we explore how the production, supply and deployment of blood products are socially mediated, drawing on theoretical perspectives from recent work on 'tissue economies'. We highlight the ways in which safety threats in the form of infections that might be transmitted through blood and plasma impact on this tissue economy and how these have led to a revaluation of donor bodies and restructuring of blood economies. Specifically, we consider these themes in relation to the management of recent threats to blood safety in the United Kingdom. We show that the tension between securing the supply of blood and its products and ensuring its safety may give rise to ethical concerns and reshape relations between donor and recipient bodies.